The psychometric properties of the Patient Health Questionnaire (PHQ-9) in a sample of individuals 40 years and older from the Icelandic population - Freyja Ágústsdóttir 1994-; Sara Daníelsdóttir 1993- (2018)
Background: The Patient Health Questionnaire (PHQ-9) is a screening measure for depressive disorders and severity of depressive symptoms. The PHQ-9 has been found to have good psychometric properties across clinical settings and in the general population. In this study, the severity of depressive symptoms in the Icelandic general population of individuals 40 years and older was assessed and compared between females and males both independent of age and across age groups. In addition, psychometric properties of the Icelandic version of the PHQ-9 were assessed. Method: Individuals born in Iceland prior to the year 1975 (i.e., 40 years or older) were offered participation and 78,582 gave consent to being screened for monoclonal gammopathy of undermined significance (MGUS). About half the individuals (i.e., 46%, n = 36,139) that provided consent to being screened for MGUS completed the PHQ-9, The Generalized Anxiety Disorder scale (GAD-7), and Satisfaction with Life Scale (SWLS), and two single item measures for happiness and health-related worry. Internal consistency, item analysis, and construct validity for the PHQ-9 were assessed. Results: Average score on the PHQ-9 was relatively low, majority of participants reported minimal to mild depressive symptoms, and did not meet the cut-off point indicating a probable major depressive disorder (MDD) diagnosis. Females reported more severe depressive symptoms and were more likely to meet the cut-off point indicating a probable MDD diagnosis, and the trend increased with increasing age. The PHQ-9 had good internal consistency (i.e., Cronbach’s α = .84) and construct validity as evident by correlations with scores on other scales, GAD-7, r (34,777) = .75, p < .001; SWLS, r (34,919) =.57, p < .001; single item measure for health-related worry, r (34,919) = .35, p < .001; single item measure for happiness, r (34,919) = -.49, p < .001, measuring concepts associated with depressive symptoms. Conclusion: An epidemiological sample of Icelandic individuals aged 40 ...